Ekshumacja żołnierzy niemieckich koło wsi Kiełpin (gm. Zielona Góra) w 2010 r. - komunikat = Exhumation of German soldiers near the village of Kiełpin (Zielona Góra commune) in 2010 - announcement - Towpik, Paweł Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
22nd September 2010, nearby the road from Kiełpin (Külpenau) to Barcikowice Małe (Klein Hänchen)in Zielona Góra district, the exhumation of eight German soldiers from the Second World War was held. The complete lack of belts and their buckles with the well-preserved leather footwear and metal buttons as well as contemporary German coins may prove that the buried were the prisoners of war. The soldiers died during a skirmish with the Red Army troop, probably in the Elary morning from 14th to 15th February 1945. Their remains were buried after the exhumation datek 5th November 2010 in the cemetery in Miłostów, Poznań.
Keywords: II (druga) wojna światowa; Ziemie Odzyskane; cmentarze wojskowe